The teacher’s communicative competence in the English language classroom: three case studies - Xavier, Rosely Perez (The ESPecialist, 2012)
This paper analyses the teaching practice of three teachers of English in three different secondary school students groups. These teachers were chosen because of their different levels of communicative competence and the way they used to make themselves understood in the target language. The data were collected through field notes. The results show that a fluent teacher may not be able to provide learning opportunities in class. Contrary to that, a less fluent teacher may be able to promote successful interaction in the target language despite his/her linguistic deficiencies. It is claimed, therefore, that the teacher of English must develop not only communicative competence in the target language but also a meaningful and cooperative interaction in the classroom.